Awake prone positioning in patients with hypoxemic respiratory failure due to COVID-19: the PROFLO multicenter randomized clinical trial - Jacob Rosén; Erik von Oelreich; Diddi Fors; Malin Jonsson Fagerlund; Knut Taxbro; Paul Skorup; Ludvig Eby; Francesca Campoccia Jalde; Niclas Johansson; Gustav Bergström; Peter Frykholm; the PROFLO Study Group (Critical Care, 2021)
Abstract Background The effect of awake prone positioning on intubation rates is not established. The aim of this trial was to investigate if a protocol for awake prone positioning reduces the rate of endotracheal intubation compared with standard care among patients with moderate to severe hypoxemic respiratory failure due to COVID-19. Methods We conducted a multicenter randomized clinical trial. Adult patients with confirmed COVID-19, high-flow nasal oxygen or noninvasive ventilation for respiratory support and a PaO2/FiO2 ratio ≤ 20 kPa were randomly assigned to a protocol targeting 16 h prone positioning per day or standard care. The primary endpoint was intubation within 30 days. Secondary endpoints included duration of awake prone positioning, 30-day mortality, ventilator-free days, hospital and intensive care unit length of stay, use of noninvasive ventilation, organ support and adverse events. The trial was terminated early due to futility. Results Of 141 patients assessed for eligibility, 75 were randomized of whom 39 were allocated to the control group and 36 to the prone group. Within 30 days after enrollment, 13 patients (33%) were intubated in the control group versus 12 patients (33%) in the prone group (HR 1.01 (95% CI 0.46–2.21), P = 0.99). Median prone duration was 3.4 h [IQR 1.8–8.4] in the control group compared with 9.0 h per day [IQR 4.4–10.6] in the prone group (P = 0.014). Nine patients (23%) in the control group had pressure sores compared with two patients (6%) in the prone group (difference − 18% (95% CI − 2 to − 33%); P = 0.032). There were no other differences in secondary outcomes between groups. Conclusions The implemented protocol for awake prone positioning increased duration of prone positioning, but did not reduce the rate of intubation in patients with hypoxemic respiratory failure due to COVID-19 compared to standard care. Trial registration ISRCTN54917435. Registered 15 June 2020 ( https://doi.org/10.1186/ISRCTN54917435 ).